Romania's EU Accession Impact on the Development of Romanian Economy - Cristian Incaltarau; Sorin-Stefan Maha (CES Working Papers, 2010)
Romania joined the EU on January 1, 2007. Becoming a full member had effects on both Romania and the European Union. Once the Association Treaty had been signed, a complex process of integration began. The integration process didn't end after Romania's EU accession but will continue to integrate the economies of all Member States. The questions that we answer are: Which were the effects felt by Romania in the pre-accession period? What happened after the accession to the European Union?
Keywords: 330; effects; negotiating; Accession Treaty; accession criteria; economic integration; European Union; Romania; impact on Romanian economy